What makes an ad funny? Is humour effective and what causes humour effects in advertising? - Doan, THI THUY DUNG (2018)
Researchers and practitioners commonly consider humour as an effective tool to enhance the persuasiveness of advertising. Yet, few studies define the humour construct. Given that ads which are intended to be humorous by advertisers may not be perceived as humorous by the audience, this study examines humour as a perceptual response by the audience by measuring the degree of perceived humour instead of manipulated humour. Under this perspective, the study seeks to re-examine the effect of humour in advertising studies. In particular, relationships between humour and persuasion outcomes including attitude towards the ad, purchase intention and word-of-mouth about the ad are studied. Based on a stimuli-driven survey, findings show that a higher degree of perceived humour is associated with a more favourable attitude towards the ad, a higher purchase intention, as well as more favourable word-of-mouth about the ad. In addition, this research extends current literature by examining whether the degree of perceived humour is affected by social influence and persuasion knowledge. Results suggest that there is a positive relationship between social influence and the degree of perceived humour and a negative relationship between persuasion knowledge and perceived humour.